(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
Among those who discuss about the concept of Justice, Amartya Sen, but also Garzón Valdés and Villoro, claim that it is more urgent to walk away from injustice, than to concentrate our efforts in finding the meaning of Justice. Here I argue that the humiliation of dignity is a good yardstick to use when we talk about the unacceptable, where the negative way towards Justice begins. For that purpose I explore the arguments of Villoro, Sen, and Nussbaum. Finally, I make clear the link between humiliation and exclusion to suggest that in some contexts, and specifically in that of injustice, the use of the concept of humiliation can result more useful than that of exclusion.